Competência comunicativa, variação estilística e canção: proposta didática para o ensino fundamental II - Mehret, Marize Aparecida Amaral (2019)
This dissertation is the result of a research directed to a didactic proposal in the teaching of, native language, with the purpose of studying, how to present the stylistic variation, from the highest to the lowest degree of stylistic monitoring, through a discursive/textual genre, the genre song. The objective is to increase students'communicative competence, starting from their linguistic knowledge and the actual uses of the language, with a view to producing a didactic material that can be a support for the Portuguese teacher, for the study of stylistic variation. The specific objectives of this study are: A) to investigate the students' musical preferences and how the PCN orientes the insertion of the song into language teaching; B) apply a didactic proposal in a 9th grade class as a goal to observe the use of language in the song genre; C) to lead students to recognize, in a more specific way, the degrees of stylistic monitoring; D) show the students the differences of registration in the use: how they present the formal and the informal; E) investigate with the students the song genre, observe the records found in it and how they are employed. To reach the proposed objectives, the research is based on studies and official documents on the teaching of the Portuguese language in Brazil; of the vast repertoire of sociolinguistic studies and Educational Sociolinguistics, starting from Bortoni-Ricardo (2004); of studies on discursive/ textual genres, more specifically in Bakhtin (1997, 2003) and Marcuschi (2002, 2003, 2008); on the characteristics, the specifics and the official recommendations of the use genre song in the classroom. The methodology adopted for conducting the research is qualitative and the procedure is action research. The results of the analysis of this proposal, applied in a 9th grade class of a public school in the administrative district of Santa Maria, Federal District, demonstrate that, through a teaching that allows the reception with empathy of the knowledge inherent to the speakers, that demystify the unfounded belief of "right" and "wrong", recognizing and respecting linguistic diversity in the classroom, it is possible to transform pedagogical practice and to promote learning in Portuguese language teaching. Key-works: Communicative competence, Portuguese language teaching; didactic proposal; stylistic variation; genre song.